Corrosion in petroleum and petrochemical industries - Mohammed Misbahul, Amin (University College of Science and Technology Terengganu, 2009)
Corrosion is the destructive result of chemical reaction between a metal or metal alloy and its environment. Metal atoms in nature are present as chemical compounds. The same amounts of energy needed to extract metals from their minerals are emitted during chemical reactions that produce corrosion. Corrosion returns the metals to its combined state in chemical compounds that are similar or even identical to the minerals from which the metals were extracted. Thus, corrosion has been called 'extractive metallurgy in reverse'.